An FtsH protease is recruited to the mitochondrion of Plasmodium falciparum. - Aiman Tanveer; Stacey M Allen; Katherine E Jackson; Manish Charan; Stuart A Ralph; Saman Habib (PLoS ONE, 2013)
The two organelles, apicoplast and mitochondrion, of the malaria parasite Plasmodium falciparum have unique morphology in liver and blood stages; they undergo complex branching and looping prior to division and segregation into daughter merozoites. Little is known about the molecular processes and proteins involved in organelle biogenesis in the parasite. We report the identification of an AAA+/FtsH protease homolog (PfFtsH1) that exhibits ATP- and Zn(2+)-dependent protease activity. PfFtsH1 undergoes processing, forms oligomeric assemblies, and is associated with the membrane fraction of the parasite cell. Generation of a transfectant parasite line with hemagglutinin-tagged PfFtsH1, and immunofluorescence assay with anti-PfFtsH1 Ab demonstrated that the protein localises to P. falciparum mitochondria. Phylogenetic analysis and the single transmembrane region identifiable in PfFtsH1 suggest that it is an i-AAA like inner mitochondrial membrane protein. Expression of PfFtsH1 in Escherichia coli converted a fraction of bacterial cells into division-defective filamentous forms implying a sequestering effect of the Plasmodium factor on the bacterial homolog, indicative of functional conservation with EcFtsH. These results identify a membrane-associated mitochondrial AAA+/FtsH protease as a candidate regulatory protein for organelle biogenesis in P. falciparum.